The Accuracy of Praziquantel Dose Poles for Mass Treatment of Schistosomiasis in School Girls in KwaZulu-Natal, South Africa. - Marije Baan; Hashini Nilushika Galappaththi-Arachchige; Silindile Gagai; Christine G Aurlund; Birgitte J Vennervald; Myra Taylor; Lisette van Lieshout; Eyrun F Kjetland (Public Library of Science (PLoS), 2016)
BACKGROUND:More than 260 million people live with schistosomiasis and regular mass-treatment should be implemented to prevent morbidity. Praziquantel, dosed at 40 milligrams per kilogram bodyweight, is the drug of choice. During the last decades the WHO Tablet Pole-which estimates tablet need by height as representing weight-has been used as a practical and cheap tool in mass treatment. In South Africa this method could be inaccurate given the prevalence of overweight and obesity. In this study in female pupils in KwaZulu-Natal, South Africa, we explored the accuracy of the WHO Tablet Pole and the recently developed Modified Dose Pole for adults with two additional intervals and correction for body mass index (BMI). METHODOLOGY:In randomly selected primary and secondary schools of schistosomiasis-endemic areas, height and weight of female pupils were measured. The WHO Tablet Pole and Modified Dose Pole were used to indicate the amount of praziquantel according to height and the dose in milligrams per kilogram bodyweight was calculated. The BMI correction was performed by adding 600 milligrams (1 tablet) to the indicated dose if a person was overweight/obese. PRINCIPAL FINDINGS:3157 female students were investigated and 35% were found to be overweight/obese. Using the WHO Tablet Pole, 73% would have received an adequate dose (range 30-60 mg/kg). When correcting for BMI, this would have been 94%. Using the Modified Dose Pole with BMI correction, 97% would have been adequately treated. CONCLUSIONS:This study shows that the WHO Tablet Pole will be inaccurate in estimating the dose of praziquantel in South African girls due to high prevalence of overweight/obesity. Under-dosing of individuals who appear overweight/obese could be largely prevented by adding an extra praziquantel tablet to the recommended dose. Further research must be done to explore if subjective weight estimates are reliable.